Molecular Characterization of Animal Fasciola Spp. Isolates from Lorestan Province, Western Iran - Peyman Heydarian; Vahid Jajarmi; Adel Spotin; Keyhan Ashrafi; Mehdi Mohebali; Mojgan Aryaeipour; Arezoo Bozorgomid; Elham Hajialilo; Mohammad Javad Abbaszadeh Afshar; Mandana Fadaei Tehrani; Mohammad Bagher Rokni (Tehran University of Medical Sciences, 2022)
Background: We aimed to detect the genetic diversity of samples identified morphologically as Fasciola spp. from sheep, cattle and goat from Lorestan Province, western Iran using PCR-RFLP method. Besides, we evaluated the genetic diversity indices, sequencing and phylogenetic analysis using mitochondrial gene (ND1 and CO1). Methods: PCR-RFLP analysis of ribosomal ITS1 fragment by RsaI restriction enzyme to investigate the genetic characteristics of Fasciola species obtained from different hosts (18 sheep, 21 cattle, and 17goats) was conducted.  The samples were sequenced. Sequences were evaluated using BLAST software and the parasite species were identified with similarity percentage and overlap with the species registered in the gene bank. Then similarity and diversity of intra-species and intra-species diversity of Fasciola species were calculated. Results: In Lorestan, based on RFLP pattern, 93% (52) of the Fasciola spp. isolates had a RFLP pattern related to F. hepatica and 7% (4) were F. gigantica. No hybrid forms were detected. The CO1 gene could clarify 19 haplotypes against ND1 gene that found 22 haplotypes among livestock. Sequencing results of the mtDNA showed intra-species identity 98. 5%-100% and Intra-species-diversity: 0-1.5% compared to the GenBank sequences. Conclusion: Using PCR-RFLP method, two species of F. hepatica and F. gigantica, were present in Lorestan Province, but F. hepatica was more prevalent. Mitochondrial genes could better test variability indices in different hosts than ribosomal genes, consequently among mitochondrial genes, the ND1 gene could better examine differences and similarities than CO1.